FTY720 Prevents Spatial Memory Impairment in a Rat Model of Chronic Cerebral Hypoperfusion via a SIRT3-Independent Pathway - Zhang, Miao; Hu, Yuan; Zhang, Jiahui; Zhang, Junjian (Frontiers in Aging Neuroscience, 2021)
Vascular dementia (VD) and Alzheimer's disease (AD) are the most prevalent types of late-life dementia. Chronic cerebral hypoperfusion (CCH) contributes to both AD and VD. Recently, accumulating evidence has indicated that fingolimod (FTY720) is neuroprotective in acute cerebral ischemic stroke animal models, and the drug is now being used in clinical translation studies. However, fewer studies have addressed the role of FTY720 in chronic cerebral hypoperfusion (CCH)-related brain damage. In the present study, to investigate whether FTY720 can improve CCH-induced spatial memory loss and its underlying mechanism, two-vessel occlusion (2VO) rats were administered intraperitoneal FTY720 (1 mg/kg) for 7 consecutive weeks from post-operative day 8. Spatial memory was tested using the Morris Water Maze (MWM), and the rats' brains were harvested to allow molecular, biochemical, and pathological tests. We found that FTY720 treatment significantly reduced the escape latency and increased the target quadrant swimming time of the 2VO rats in the MWM task. The improvement in memory performance paralleled lower levels of pro-inflammatory cytokines and Iba-1 positive cells in the hippocampus of the 2VO rats, indicating that FTY720 had a beneficial effect in mitigating neuroinflammation. Furthermore, we found that FTY720 alleviated mitochondrial dysfunction in 2VO rats, as manifested by lower malondialdehyde levels, higher ATP content, and upregulation of ATP synthase activity in the hippocampus after treatment. FTY720 had no effect on the CCH-induced decrease in the activity of hippocampal Sirtuin-3, a master regulator of mitochondrial function and neuroinflammation. In summary, the results showed that FTY720 can improve CCH-induced spatial memory loss. The mechanism may involve Sirtuin-3-independent regulation of mitochondrial dysfunction and neuroinflammation in the hippocampus. The present study provides new clues to the pathological mechanism of CCH-induced cognitive impairment.